KAREKTERISASI EKSTRAK ETANOL UBI JALAR UNGU (Ipomea batatas L) MENGGUNAKAN SPEKTROSKOPI INFRARED - Muhammad Yasser; Muhammad Badai (Cokroaminoto Journal of Chemical Science, 2019)
Purple Sweet Potato extraction has been done by soaking with ethanol solvent for 24 hours. Ethanol extract was then characterized using Infrared spectroscopy to determine the functional groups contained in the extract. Characterization results using Infrared spectroscopy showed wave number 1053.17 cm-1 as a marker for aromatic groups, wave number 1276.92 cm-1 indicates the presence of primary or secondary OH bonds, wave number 1413.87 indicates the presence of OH bonds as phenols, wave number 1637.62 indicates the C = C bond, wave number 2941.54 shows the CH bond and wave number 3410.26 also indicates the presence of an OH group.